How do transitory income shocks affect investment in agriculture? Evidence from exchange rate shocks in Bangladesh - Boote, Sophie (Oxford Department of International Development, 2021)
Transitory income shocks affect many poor families in developing countries and can affect household investments, consumption, and labor supply decisions through a variety of chan nels and with theoretically ambiguous net effects. Using detailed household survey data, this paper exploits a quasi-experiment in Bangladesh in which differential exchange rate shocks across migrant destinations provide an exogenous source of variation in the remittance in come, an important supplement to household earnings, received by their origin households. The results show that positive shocks to income cause an increase in household investment and household labor supply, although this effect varies across men and women.